Leadership for global systemic change : beyond ethics and social responsibility - Robinson-Easley, Christopher Anne (Palgrave Macmillan, 2017)
This book argues that organizations, corporations, and governments have the abilities and resources to drive deep systemic change, yet fail to evoke change strategies that can significantly improve the social fabric of our global environment. It actively engages the reader in a conversation that reviews, evaluates, and challenges these issues juxtaposed to current strategies and resulting positions regarding business ethics, social responsibility, our view towards humanity, and the role of leaders. Provocative in its voice and message, this book demonstrates how more robust contributions can lead to effective change. The author includes a detailed change model designed to invoke significant global change that builds upon the current work of the United Nations' Global Compact, and incorporates the participation of all critical stakeholders including corporate leaders, civil society, government leaders, and the people who are challenged daily by ethical dilemmas and social responsibility initiatives. It speaks to academics and students of change management, social responsibility, and business ethics, as well as the organizations and communities who stand to make a positive difference in the world.
Keywords: Industrial management -- Environmental aspects.; International business enterprises.; Social responsibility of business.; Business ethics.; elektronické knihy; electronic books